Students’ Perceptions of Synthetic Voice Technology in EFL Listening Comprehension - Purnama Hanan Murod; Flora; Muhammad Sukirlan (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study investigated student perceptions of artificial intelligence (AI)-generated synthetic voice technology as primary listening texts in English language instruction. A perception questionnaire comprising 8 Likert-scale questionnaire items was administered to 30 eleventh-grade students at MA N 1 Bandar Lampung. The instrument assessed five dimensions: clarity, naturalness, comprehension, engagement/motivation, and overall acceptance. Data analysis used descriptive statistics with mean scores and percentage distributions. Using Davis' Technology Acceptance Model, strong perceived usefulness outweighs moderate ease-of-use limitations. The instruction clarity problem represents a known technical challenge with documented solutions: reduced speech rate for instructions, simplified syntax, and enhanced audio production. Synthetic voice technology represents a viable educational tool, technical implementation prioritizes audio quality, and technology serves as scaffolding enabling student agency. Targeted technical improvements can address clarity limitations while preserving substantial educational value.